1993
DOI: 10.4039/ent125931-5
|View full text |Cite
|
Sign up to set email alerts
|

Acrocerid (Insecta: Diptera) Life Histories, Behaviors, Host Spiders (Arachnida: Araneida), and Distribution Records

Abstract: The Canadian Entomologist 125: 931-944 (1993) The family Acroceridae (Tnsecta: Diptera; "Small Headed Flies") are a seldom seen yet cosmopolitan group of endopansitoids of spiders. Recent host and distribution records are presented here for six species of acrocerids: Ogcodes bnreulis Cole. 1919; Ogcoir'es pu/lidipennis (Loew. 1866); Ogcodes sp. ; Acroceru bimucularu Loew. l8*, Turbopsebiur srtlphuripes (loew, 1869); and Exetasis eickstedtae Schlinger, 1972. New hosts for each fly species are: 0. borealis-S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
19
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 13 publications
1
19
0
2
Order By: Relevance
“…Dermestid larvae (Coleoptera) parasitize captive Brachypelma smithi (Pickard-Cambridge 1897) specimens (Paré et al 2001). Species of two Diptera families, Phoridae (Weinman & Disney 1997) and Acroceridae (von Eickstedt 1971(von Eickstedt , 1974Cady et al 1993), have also been reported as tarantula parasitoids.…”
mentioning
confidence: 99%
“…Dermestid larvae (Coleoptera) parasitize captive Brachypelma smithi (Pickard-Cambridge 1897) specimens (Paré et al 2001). Species of two Diptera families, Phoridae (Weinman & Disney 1997) and Acroceridae (von Eickstedt 1971(von Eickstedt , 1974Cady et al 1993), have also been reported as tarantula parasitoids.…”
mentioning
confidence: 99%
“…Interestingly, it is also possible that the manipulation of spiders by another taxonomical group, Diptera larvae of Acroceridae, involves the same hormone. These endoparasites of spiders also induce behavioral changes in web building behaviors that result in web designs similar to those of molting webs [35,36]. …”
Section: Discussionmentioning
confidence: 99%
“…Some species feed at flowers, and may be specialized pollinators, as suggested by their long proboscises (often equal to their body length), nectar feeding habits and pollen loads (Borkent and Schlinger 2008a, b). All species with known immature habits are parasitoids of spiders (Schlinger 1981, 1987; Cady et al 1993; Larrivée and Borkent 2009). …”
Section: Introductionmentioning
confidence: 99%